Overview of the genetic tools in the Archaea - Atomi, Haruyuki; Imanaka, Tadayuki; Fukui, Toshiaki (Frontiers in Microbiology, 2012)
This section provides an overview of the genetic systems developed in the Archaea. Genetic manipulation is possible in many members of the halophiles, methanogens, Sulfolobus and Thermococcales. We describe the selection/counterselection principles utilized in each of these groups, which consist of antibiotics and their resistance markers, and auxotrophic host strains and complementary markers. The latter strategy utilizes techniques similar to those developed in yeast. However, Archaea are resistant to many of the antibiotics routinely used for selection in the Bacteria, and a number of strategies specific to the Archaea have been developed. In addition, examples utilizing the genetic systems developed for each group will be briefly described.